Involvement of Rat Hippocampal Astrocytes in β-Amyloid-Induced Angiogenesis and Neuroinflammation - L. Fioravanzo; M. Venturini; R. D. Liddo; F. Marchi; C. Grandi; P. P. Parnigotto; M. Folin (Current Alzheimer Research, 2010)
Although Alzheimer's disease (AD) is considered a neurodegenerative disorder, in the last few years a large amount of evidence has suggested that it is also a vascular pathology characterized by increased capillary density and expression of angiogenic factors. In AD the endothelium degenerates, promoting local neuroinflammation and activation of brain endothelium, perivascular microglia, pericytes, astrocytes. Excess tumor necrosis factor (TNF) in the cerebrospinal fluid (CSF), at a concentration of 25 times higher than in the control group, has been demonstrated in AD. Recent studies provide evidence that treatment with TNF-α antagonists may result in a rapid cognitive improvement in AD patients. In the present work we investigated the role of astrocytes in AD angiogenesis and neuroinflammation by means of conditioned media of untreated and Aβ-treated rat hippocampal astrocytes (RHAs) on rat microvascular endothelial cells (RCECs). The results demonstrated that RHA media increase RCEC proliferation and capillary-like structure formation. Moreover RHAs secrete IL-1β and, only after the Aβ1-42 treatment, TNF-α promotes RCEC release of IL-1β, IL-6 and TNF-α. The removal of IL-1β, TNF-α and/or VEGF, a strong angiogenic inducer highly over-expressed in AD brains, by means of specific antibody-coated beads in RHA media affects RCEC release of IL-1β, IL-6 and TNF-α. We hypothesised that astrocytes contribute to AD angiogenesis and neuroinflammation by the direct release of pro-inflammatory cytokines. The effect of an anti-inflammatory agent, such as etanercept, decreased RCEC in vitro cytokine release. This could be compared to the effect found in our experiments with antibody anti TNF-α-coated beads.
Keywords: RCEC Proliferation